Working on the inside: Ronald Dworkin's Moral Philosophy - Kramer, Matthew H. (Derecho y Humanidades, 2016)
In my 2009 book Moral Realism as a Moral Doctrine, I argued that morality is objective in several distinct though overlapping senses, and I further maintained that questions about the objectivity of morality are substantive moral questions (albeit usually at high levels of abstraction). In the course of that book, I made several laudatory references to Ronald Dworkin’ s well-known 1996 article ‘ Objectivity and Truth’ as well as to some of his other writings. In regard to the two main themes of my book that have just been mentioned, I took myself to be firmly allied with Dworkin. Though Moral Realism as a Moral Doctrine adverts only occasionally to his work, it makes clear my esteem for his reconception of meta-ethics as a branch of ethics. At a few other junctures in my 2009 volume, however, I criticized Dworkin. My criticisms were focused not on his legal philosophy ─ with which I have sustainedly taken issue elsewhere ─ but instead on some of his ethical positions. One such position to which I took exception is his value-monism. That is, I took exception to his opting for the hedgehog side of the ancient hedgehog/fox dichotomy that was made famous in modern times by Isaiah Berlin. Dworkin’ s allegiance to the former side of that dichotomy is starkly proclaimed by the title of his sprawlingly ambitious recent book Justice for Hedgehogs. In what follows, I will leave aside many sections of that impressive tome in order to concentrate on the main portion that deals with meta-ethics and on one portion that deals with the putative unity of value. Given that I am almost entirely in agreement with the former portion and largely in disagreement with the latter, this brief review will naturally impugn Dworkin’ s assumption that his anti-Archimedeanism and his value-monism are integrally connected